Development of a Smartphone Recommendation System Based on the TOPSIS Method for Multi-Criteria Selection - Verdyansyah Pratama, Rafly; Hasrullah, Hasrullah (Riviera Publishing, 2025)
The rapid development of smartphone technology presents a variety of options for consumers, making purchasing decisions increasingly complex. This research aims to design a decision support system based on the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. The system is designed to help consumers choose smartphones based on criteria such as camera, battery, price, RAM, and performance. The research process involves collecting data through interviews, observations, and literature studies; determination of criteria; normalization of the matrix; weighting; and calculation of preference values. The results showed that the TOPSIS method was effective in providing accurate and relevant recommendations, with Xiaomi Mi Note 10 as the best choice in this study. The system proved to be efficient and satisfying to the users, although improvements to the interface and additional features were suggested for further development. This study proves that the TOPSIS method can be applied efficiently in the context of smartphone selection, providing real benefits for consumers in choosing the product that best suits their needs and preferences.